Untapped potential in Australian hospitals for organ donation after circulatory death. Issue 7 (25th September 2017) - Rakhra, Sandeep S; Opdam, Helen I; Gladkis, Laura; Arcia, Byron; Fink, Michael A; Kanellis, John; Macdonald, Peter S; Snell, Gregory I; Pilcher, David V
Abstract: Objective: To determine the potential for organ donation after circulatory death (DCD) in Australia by applying ideal and expanded organ suitability criteria, and to compare this potential with actual DCD rates. Design: Retrospective cohort study. Setting, methods: We analysed DonateLife audit data for patients aged 28 days to 80 years who died between July 2012 and December 2014 in an intensive care unit or emergency department, or who died within 24 hours of discharge from either, in the 75 Australian hospitals contributing data to DonateLife. Ideal and expanded organ donation criteria were derived from international and national guidelines, and from expert opinion. Potential DCD organ donors were identified by applying these criteria to patients who had been intubated and were neither confirmed as being brain‐dead nor likely to have met brain death criteria at the official time of death. Results: 8780 eligible patients were identified, of whom 202 were actual DCD donors. For 193 potential ideal (61%) and 313 potential expanded criteria DCD donors (72%), organ donation had not been discussed with their families; most were potential donors of kidneys (416 potential donors) or lungs (117 potential donors). Potential donors were typically older, dying of non‐neurological causes, and more frequently had chronic organ disease than actual donors. Identifying all these potential donors, assuming a consent rate of 60%, would have increased Australia's donation rate from 16.1 to 21.3 per million population in 2014. Conclusions: The untapped potential for DCD in Australia, particularly of kidneys and lungs, is significant. Systematic review of all patients undergoing end‐of‐life care in critical care environments for donor suitability could result in significant increases in organ donation rates.